A sensitive UPLC–MS/MS method for simultaneous determination of polyphenols and theaflavins in rat plasma: Application to a pharmacokinetic study of Da Hong Pao tea. (4th February 2019) - Wang, Lin; Yan, Ting; Zhang, Kexia; Li, Feifeng; Jia, Jingming; Hu, Gaosheng
Abstract: A method based on ultra‐performance liquid chromatography–tandem mass spectrometry has been developed for the rapid and simultaneous determination of five catechins and four theaflavins in rat plasma using ethyl gallate as internal standard. The pharmacokinetic profiles of these compounds were compared after oral administration of five kinds of Da Hong Pao tea to rats. Biosamples processed with a mixture of β ‐glucuronidase and sulfatase were extracted with ethyl acetate–isopropanol. Chromatographic separation was achieved by gradient elution using 10 mm HCOONH4 solution and methanol as the mobile phase. Analytes were detected using negative ion electrospray ionization in multiple reaction monitoring mode. The lower limits of quantification were 1.0, 0.74 and 0.5 ng/mL for theaflavins, two catechins and three catechins, respectively. The validation parameters were well within acceptable limits. The average half‐lives ( t 1/2 ) in blood of the reference solution group was much shorter than those of tea samples. The values of AUC0– t and C max of the polyphenols and theaflavins exhibited linear pharmacokinetic characteristics which were related to the dose concentration.